Master of spies : the memoirs of General Frantisek Moravec - d (Garden City, N.Y. : Doubleday, 1975)
The author describes his life from his early soldiering in World War I through his years as head of Czech Intelligence to his escape from Czechoslovakia after the Communists took over in 1948.
Moravec, Frantisek, 1895-or 6 -- 1966. Espionage-Chechoslovak Republic-History.
Keywords: d; d; 1900-1999; Espionage -- Czechoslovakia -- History -- 20th century; Spies -- Czechoslovakia -- History -- Biography; Autobiography; Biographies; History